Rethinking Database Algorithms for Phase Change Memory - Chen, Shimin; Gibbons, Phillip B.; Nath, Suman (CIDR'11: 5th Biennial Conference on Innovative Data Systems Research, 2011)
Phase change memory (PCM) is an emerging memory technology with many attractive features: it is non-volatile, byte-addressable, 2–4X denser than DRAM, and orders of magnitude better than NAND Flash in read latency, write latency, and write endurance. In the near future, PCM is expected to become a common component of the memory/storage hierarchy for a wide range of computer systems. In this paper, we describe the unique characteristics of PCM, and their potential impact on database system design. In particular, we present analytic metrics for PCM endurance, energy, and latency, and illustrate that current approaches for common database algorithms such as B+-trees and Hash Joins are suboptimal for PCM. We present improved algorithms that reduce both execution time and energy on PCM while increasing write endurance.